Mediating role of systemic inflammation on the association between periodontitis and gestational diabetes mellitus: a cross-sectional study - Jing Cheng; Qi Jiang; Yang Liu; Shengdan Zhang; You Wang; Dai Lin; Bo Cheng (BMC Oral Health)
Abstract Objectives This study aimed to explore the relationship between periodontitis and gestational diabetes mellitus (GDM) and to ascertain the role of systemic inflammation in mediating this association. Methods Data from 5,283 women of reproductive age ranging from 20 to 44 years were retrieved from the National Health and Nutrition Examination Survey (NHANES) III (1988–1994) and NHANES 2009–2014 cycles. The female participants were categorized into three groups: non-diabetes, DM, and GDM. Multivariate logistic and linear regression models were employed to assess the correlations between periodontal variables and diabetes status. Additionally, a mediation analysis was performed to explore the role of systemic inflammatory biomarkers. Results Compared to non-periodontitis, women with periodontitis have a 1.68 times higher risk of having GDM (OR = 1.68, 95% CI: 1.14–2.50). Clinical attachment level (CAL), the continuous periodontal parameter, also presented a significant association with GDM risk (OR = 1.50, 95% CI: 1.25–1.81 per 1-mm increase). Linear regression analyses further revealed that hemoglobin A1c (HbA1c) levels were positively associated with periodontitis (Beta = 0.19, SE = 0.06, p < 0.01) and CAL (Beta = 0.06, SE = 0.03, p < 0.001), respectively. The association between periodontitis and GDM risk was found to be mediated by white blood cell count (WBC), monocyte count, and monocyte-lymphocyte ratio (MLR), with mediation proportions of 5.02%, 5.88%, and 5.20%, respectively. Similar mediation effects were observed for the CAL-GDM association. Conclusions The present study indicated that periodontitis was associated with GDM among women of childbearing age, with systemic inflammation potentially serving as a partial mediator of this association.